The Ability - Vaughan, M. M. (Vaughan, M. M. Ability., 2013)
While Chris and five other twelve-year-olds learn to make the most of their mental abilities in a secret, government-run school last used in 1977, twins Ernest and Mort are studying under someone with much more sinister motives.